Bibliotecas públicas e ciberviolência em tempos de uma sociedade em rede: Novos papéis diante de um novo fenômeno - Ferreira, Rubens da Silva (2012)
It reflects about the role of public libraries in users' education to the knowledge of cyberviolence. This phenomenon is expressed through of the Information and Communication Technology (ICT), which are used to cause damage to victims. The work is based on three cases of cyberviolence: a murder, an extortion and one of pedophilia. The cases help to reflect about the necessity of intervention activities of the public libraries. The theoretical table that supplies to the analysis is aided by theoretical contributions of Information Science, Sociology and Anthropology. The results show the need of involvement of the public libraries in combating of cyberviolence, because they function as users' attraction center to access information on the Internet